Nano-Engineering of Molecular Films by Self-Assembly and Langmuir-Blodgett Techniques - Enriquez, Erwin P (Archīum Ateneo, 1998)
The availability of sophisticated and ultra-sensitive analytical tools and the maturity of organic synthesis have opened new possibilities for fabrication of molecular materials designed at the nanometer scale. Presently, the most promising and widely investigated methodologies are the self-assembly and Langmuir-Blodgett procedures. The former relies on the strong, preferential affinity of specific functional groups to solid surfaces, whereas the latter involves transfer of pre-formed mono layers at the air-water interface onto solid substrates. These techniques and their recent applications are reviewed.